Conversations with Glenn Gould - Gould, Glenn 1932-1982; Cott, Jonathan (Boston Little, Brown, 1984)
One of the most idiosyncratic and charismatic musicians of the twentieth century, pianist Glenn Gould (1932-82) slouched at the piano from a sawed-down wooden stool, interpreting Bach, Beethoven, and Mozart at hastened tempos with pristine clarity. A strange genius and true eccentric, Gould was renowned not only for his musical gifts but also for his erratic behavior: he often hummed aloud during concerts and appeared in unpressed tails, fingerless gloves, and fur coats. In 1964, at the height of his controversial career, he abandoned the stage completely to focus instead on recording and writing. Jonathan Cott, a prolific author and poet praised by Larry McMurtry as "the ideal interviewer," was one of the very few people to whom Gould ever granted an interview. Cott spoke with Gould in 1974 for Rolling Stone and published the transcripts in two long articles; after Gould's death, Cott gathered these interviews in Conversations with Glenn Gould, adding an introduction, a selection of photographs, a list of Gould's recorded repertoire, a filmography, and a listing of Gould's programs on radio and TV. A brilliant one-on-one in which Gould discusses his dislike of Mozart's piano sonatas, his partiality for composers such as Orlando Gibbons and Richard Strauss, and his admiration for the popular singer Petula Clark (and his dislike of the Beatles), among other topics, "Conversations with Glenn Gould" is considered by many, including the subject, to be the best interview Gould ever gave and one of his most remarkable performances.
"Canadian Broadcasting Corporation private Glenn Gould tape collection": p. [151]-153.
Discography: p. [139]-150.
Filmography: p. [158]-159.
Keywords: Pianist; Interview